2021
DOI: 10.3390/s21093154
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Hip and Ankle Worn Actigraph Accelerometers for Measuring Steps as a Function of Gait Speed during Steady State Walking and Continuous Turning

Abstract: This study aimed to investigate the accuracy and reliability of hip and ankle worn Actigraph GT3X+ (AG) accelerometers to measure steps as a function of gait speed. Additionally, the effect of the low frequency extension filter (LFEF) on the step accuracy was determined. Thirty healthy individuals walked straight and walked with continuous turns in different gait speeds. Number of steps were recorded with a hip and ankle worn AG, and with a Stepwatch (SW) activity monitor positioned around the right ankle, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Only one article reported the criterion validity of ActiGraph type for both step counting and distance. Experiments were performed in older adults (n = 4) [ 1 , 10 , 16 , 50 ] and in adults (n = 16) [ 11 , 22 , 24 , 25 , 27 , 51 61 ]. In one study, assessment was performed in adults and older adults [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one article reported the criterion validity of ActiGraph type for both step counting and distance. Experiments were performed in older adults (n = 4) [ 1 , 10 , 16 , 50 ] and in adults (n = 16) [ 11 , 22 , 24 , 25 , 27 , 51 61 ]. In one study, assessment was performed in adults and older adults [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, we could have placed the sensors on the ankle to enhance step sensitivity. A study by Bezuidenhout et al [ 39 ] on ActiGraph monitors has shown ankle placement to be more sensitive in measuring steps than hip worn placement monitors. However, we chose to place the monitors on the thigh as this is the placement suggested by the developers of both ActivPAL and SENS.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, in the HoPE-MOR study, the ActiGraph was worn on the ankle, shown to be a more sensitive sensor placement than hip placement. 40 Thus, some of the difference in the number of steps detected in the two samples may be indicative of the sensor placements.…”
Section: Discussionmentioning
confidence: 99%